Assessment of the relationship between the maxillary sinus and the canine root tip using cone beam computed tomography - Leila Khojastepour; Najmeh Movahhedian; Mohadeseh Zolghadrpour; Mohammad Mahjoori-Ghasrodashti (BMC, 2021)
Abstract Background The purpose of the present study is to investigate the relationship between the maxillary sinus and the canine root apices in cone beam computed tomographic images (CBCT) and to assess the amount of extension of the maxillary sinus to the anterior region of the jaw in different sexes and age groups. Methods CBCT of 300 individuals (154 males and 146 females) over 20 years (with a mean age of 35.12 ± 8.40 years) were evaluated. The subjects were categorized into three age groups (20-30, 30-40, and 40-50 years). When the maxillary sinus extended to the canine area, the vertical distance between them was measured, and their relationship was classified into three types: I (more than 2 mm distance), II (less than 2 mm distance or in-contact), and III (interlock). Results 413 out of 600 maxillary sinuses (68.8%) were extended into the canine area or beyond. Among them, 15 maxillary sinuses pneumatized into the incisor area (2.5%). The prevalence of the maxillary sinuses extended to the anterior region of the jaw was not significantly different between genders. However, it was significantly less frequent in the older age group and more frequent on the left side. In addition, the mean amount of anterior extension of the maxillary sinus (mm) was significantly lower in the older age group. Type I was the most frequent vertical relationship between the maxillary sinuses and canine apices with no significant difference in gender, side, and age groups. Conclusions In most cases, the maxillary sinus extended to the canine area and sometimes reached the incisor region. This necessitates paying more attention to the maxillary anterior sextant during surgical procedures.